1993
DOI: 10.1111/j.1471-4159.1993.tb13651.x
|View full text |Cite
|
Sign up to set email alerts
|

Striatal L‐DOPA Decarboxylase Activity in Parkinson's Disease In Vivo: Implications for the Regulation of Dopamine Synthesis

Abstract: L-DOPA is a large neutral amino acid subject to transport out of, as well as into, brain tissue. Competition between dopamine synthesis and L-DOPA egress from striatum must favor L-DOPA egress if decarboxylation declines relatively more than transport in Parkinson's disease. To test this hypothesis, we injected patients with Parkinson's disease with a radiolabeled analogue of L-DOPA and recorded regional brain radioactivity as a function of time by means of positron emission tomography. We simultaneously estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 19 publications
2
36
0
1
Order By: Relevance
“…It supports the speculation that the rate constant of DDC is regulated to optimize or adjust dopamine synthesis in living brain (Buckland et al, 1992;Zhu et al, 1992;Gjedde et al, 1993;Cumming et al, 1995).…”
Section: Discussionmentioning
confidence: 67%
“…It supports the speculation that the rate constant of DDC is regulated to optimize or adjust dopamine synthesis in living brain (Buckland et al, 1992;Zhu et al, 1992;Gjedde et al, 1993;Cumming et al, 1995).…”
Section: Discussionmentioning
confidence: 67%
“…However, in the living brain the DDC activity influences the fraction of substrate, which is directed to catecholamine synthesis rather than being exported from the brain. The presence of alternate fates for L-DOPA in vivo requires that regulation of DDC must also influence the rate of DA synthesis Gjedde et al, 1993). In support of this claim, the DDC activity in the striatum of living rats was potentiated by acute neuroleptic treatment and decreased by the DA presynaptic autoreceptor agonist apomorphine (Cumming et al, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…Regulation of AADC by serotonergic receptors (Neff et al, 2006) and Nmethyl-D-aspartate (NMDA) glutamatergic receptors (Hadjiconstantinou et al, 1995;Fisher et al, 1998) has also been reported. There is also some evidence for AADC regulation associated with systemic lupus erythematosus (Bengtsson et al, 2016), Parkinson' disease (Gjedde et al, 1993), and schizophrenia (Reith et al, 1994). In experimental animals, regulation of AADC after spinal cord injury has also been reported Wienecke et al, 2014;Azam et al, 2015).…”
Section: Vertebrate Trace Aminesmentioning
confidence: 98%